Zero to one : notes on start ups, or how to build the future - Thiel, Peter, 1967-; Masters, Blake (London : Virgin Books, 2014)
What Valuable Company Is Nobody Building? The next Bill Gates will not build an operating system. The next Larry Page or Sergey Brin won't make a search engine. If you are copying these guys, you aren't learning from them. It's easier to copy a model than to make something new: doing what we already know how to do takes the world from 1 to n, adding more of something familiar. Every new creation goes from 0 to 1. This book is about how to get there.
Preface: Zero to one -- The challenge of the future -- Party like it's 1952 -- All happy companies are different -- The ideology of competition -- Last mover advantage -- You are not a lottery ticket -- Follow the money -- Secrets -- Foundations -- The mechanics of Mafia -- If you build it, will they come? -- Man and machine -- Seeing green -- The founder's paradox -- Conclusion: Stagnation or singularity? -- Acknowledgments -- Illustration credits -- Index.
Includes index.
Also issued online.
Keywords: New business enterprises; Computer software industry